1986
DOI: 10.1149/1.2108689
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Semiconductive Poly‐1,4‐Dimethoxybenzene and Its Derived Polyquinone

Abstract: Poly‐1,4‐dimethoxybenzene has been synthesized by the anodic oxidation of 1,4‐dimethoxybenzene in aprotic electrolytes. The black polymer is a doped semiconductor as formed. This material is converted to polymeric (oligomeric) hydroquinone and quinone. The polymers are insoluble in all common solvents except for the polyhydroquinone in aqueous base. A coulombic titration of this quinone, using an electrode compounded with carbon and in an aprotic electrolyte, gave an equivalent weight corresponding to ∼0.5e − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 5 publications
(15 reference statements)
1
44
0
3
Order By: Relevance
“…This principle was confirmed for CAT and somewhat for RES (Table 3); however it did not hold for HQ showing correlation with the proximity of hydroxyls in benzene ring on E FB -E max dependence. References for electrochemical oxidative polymerization of HQ (Levine et al, 2005b;Foos and Erker, 1986;Yamamoto et al, 1990) and CAT (Davis et al, 1997) can be found in literature. No literature data for electrochemi- Summarizing, below positive 0.6 V (below CAT and HQ polymerization potential at Al), correlation between the position of hydroxyl group and E FB , determined by MS analysis was observed.…”
Section: Mott-schottky Analysismentioning
confidence: 99%
“…This principle was confirmed for CAT and somewhat for RES (Table 3); however it did not hold for HQ showing correlation with the proximity of hydroxyls in benzene ring on E FB -E max dependence. References for electrochemical oxidative polymerization of HQ (Levine et al, 2005b;Foos and Erker, 1986;Yamamoto et al, 1990) and CAT (Davis et al, 1997) can be found in literature. No literature data for electrochemi- Summarizing, below positive 0.6 V (below CAT and HQ polymerization potential at Al), correlation between the position of hydroxyl group and E FB , determined by MS analysis was observed.…”
Section: Mott-schottky Analysismentioning
confidence: 99%
“…Quinone-based materials have been studied as another type of organic active material since the 1980s, since the quinone skeleton shows a two-electron redox reaction [10][11][12]. The quinone skeleton is frequently found in biological molecules, such as vitamin K, coenzyme Q 10 (ubiquinone) and plastoquinone [13][14][15], and some quinone derivatives play important roles as redox materials in biological electron-transport systems [15].…”
Section: Introductionmentioning
confidence: 99%
“…If we could use a redox system that includes 1,4-benzoquinone, which is the simplest quinine derivative, as a positive-electrode material, a large capacity of up to about 500 mAh g −1 should be expected, although the use of 1,4-benzoquinone itself is practically difficult because of its high capacity for sublimation. Several pioneering works have tried to apply this redox reaction to battery systems through the synthesis of various polymers [3,[10][11][12]. However, the two-electron redox reaction in battery materials has not been realized in most cases due to various problems, such as the dissolution of these organic compounds into the electrolytes, the instability of intermediate radical species, and low electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…90 There has been interest in using quinones in batteries for a long time. [91][92][93] Recently, poly(vinylanthraquinone) polymer immersed in 30 wt % NaOH or KOH solutions was found to exhibit a capacity of 123 mWh/ g and stability for over 500 cycles as a rechargeable air battery (Figure 16(a)). 94 The redox current increased dramatically going from neutral to basic pH, and this was explained by better electrolyte permeation in basic pH due to the swelling of polymer chains from charge repulsion between negative Q 2−…”
mentioning
confidence: 99%